2019
DOI: 10.1155/2019/6753541
|View full text |Cite
|
Sign up to set email alerts
|

The Haematological Effects of Oleanolic Acid in Streptozotocin-Induced Diabetic Rats: Effects on Selected Markers

Abstract: Background Sustained hyperglycaemia leads to the development of haematological alterations which, if left untreated, is associated with cardiovascular complications. Insulin is the mainstay drug in type 1 diabetes mellitus (T1D); however, the use of insulin is associated with haematological alterations that could further worsen cardiovascular complications. Therefore, the aim of the study was to investigate the haematological effects of oleanolic acid (OA) in streptozotocin- (STZ-) induced diabetic rats. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
(50 reference statements)
1
5
1
Order By: Relevance
“…The result of mean corpuscular volume MCV in the diabetic group was reduced compared with control. The result is consistent with the findings of [52,46] in diabetic rats. Mean corpuscular volume is the average size and volume of red blood cell which help in the determination of aetiology of anaemia.…”
Section: Discussionsupporting
confidence: 93%
“…The result of mean corpuscular volume MCV in the diabetic group was reduced compared with control. The result is consistent with the findings of [52,46] in diabetic rats. Mean corpuscular volume is the average size and volume of red blood cell which help in the determination of aetiology of anaemia.…”
Section: Discussionsupporting
confidence: 93%
“…25 OA has also been shown to have beneficial antioxidant effects on red blood cells in streptozotcin-induced diabetic rats. 27 The differences in these studies compared to the current one can possibly be attributed to different experimental models used to investigate the effect of OA on the heart. We used a high fructose diet while the previous studies used chemically induced methods.…”
Section: Oleanolic Acid On Oxidative Stress Biomarkersmentioning
confidence: 85%
“…In contrast, earlier study reported a significant increment in RBC indices, such as RBCs, Hb, Hct, and RDW, in prediabetic rats compared with healthy control rats. This condition is probably caused by a state of hyperinsulinemia, where insulin acts as a cofactor in the erythropoiesis process, resulting in an increase in the RBC value [13].…”
Section: Discussionmentioning
confidence: 99%